Species profiles life histories and environmental requirements of coastal fishes and invertebrates (Pacific Northwest)--Pacific geoduck clam - Goodwin, C.Lynn; Pease, Bruce (Washington, D.C. U.S. Department of the Interior, 1989)
U. S. Fish and Wildlife Service. Biological report ; 82(11.120)
Keywords: Pacific geoduck clam--Pacific Northwest